2015
DOI: 10.1016/j.apradiso.2015.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Polymer gel dosimeter based on itaconic acid

Abstract: A new polymeric dosimeter based on itaconic acid and N, N'-methylenebisacrylamide was studied. The preparation method, compositions of monomer and crosslinking agent and the presence of oxygen in the dosimetric system were analyzed. The resulting materials were irradiated with an X-ray tube at 158cGy/min, 226cGymin and 298cGy/min with doses up to 1000Gy. The dosimeters presented a linear response in the dose range 75-1000Gy, sensitivities of 0.037 1/Gyat 298cGy/min and an increase in the sensitivity with lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Various studies have analyzed the MRI response of polymer gels for possible application in radiotherapy dose mapping ( [58,63] and references therein). In particular, polymer gels have been investigated for dosimetry in conformal therapy, IMRT, IMAT, IGRT, VMAT and tomotherapy [55,70,83,88,102,, small photon fields [136][137][138], stereotactic radiosurgery [55,[139][140][141][142], 60-cobalt source [143,144], brachytherapy [55,85,92,[145][146][147][148][149], cyberknife [150], gamma-knife [151], low-energy X-rays [152,153], high-LET and proton therapy [55,154,155], boron capture neutron therapy [55,[156][157][158][159], for interface dosimetry in the presence of tissue inhomogeneities [55,160,161], for X-ray tubes [162] and for diagnostic nuclear medicine [163]. Recently, polyacrilamide gels were proposed for dosimetry and end-to-end test for MRI-linac apparatus [164]…”
Section: Characterization and Performancementioning
confidence: 99%
“…Various studies have analyzed the MRI response of polymer gels for possible application in radiotherapy dose mapping ( [58,63] and references therein). In particular, polymer gels have been investigated for dosimetry in conformal therapy, IMRT, IMAT, IGRT, VMAT and tomotherapy [55,70,83,88,102,, small photon fields [136][137][138], stereotactic radiosurgery [55,[139][140][141][142], 60-cobalt source [143,144], brachytherapy [55,85,92,[145][146][147][148][149], cyberknife [150], gamma-knife [151], low-energy X-rays [152,153], high-LET and proton therapy [55,154,155], boron capture neutron therapy [55,[156][157][158][159], for interface dosimetry in the presence of tissue inhomogeneities [55,160,161], for X-ray tubes [162] and for diagnostic nuclear medicine [163]. Recently, polyacrilamide gels were proposed for dosimetry and end-to-end test for MRI-linac apparatus [164]…”
Section: Characterization and Performancementioning
confidence: 99%
“…However, the use of more direct techniques like Raman spectroscopy could provide a precise insight on changes in the chemical structure of sample constituents and, therefore, offers a unique tool to study the polymerization taking place in the dosimeters. In that regard, Baldock et al (Baldock et al, 1998) were the first to use Raman spectroscopy for the study of monomer consumption in irradiated polymer gel dosimeters, and since then several studies on the use of Raman spectroscopy with different polymer gel dosimetry were reported (Adenan et al, 2014;Huang et al, 2013;Jirasek, 2010;Mattea et al, 2015a;Rintoul et al, 2003), which show the potentiality of the technique to evaluate the consumption of each reactive species separately, and also to study more complex mechanisms taking place in the gels like the interaction between typical antioxidants with the monomers, gelatin or other species present in the dosimeter.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This study showed that, if concentrations lower than w v 0.50% / of GTA were used to crosslink the gelatin matrix, its thermal stability was significantly improved and an increase of the elastic modulus up to 100 times was achieved at ∘ C 37 . In addition, the analytical responses of crosslinked and unmodified itaconic acid based dosimeters (Mattea et al, 2015) were compared with no significant differences between each other.…”
Section: Introductionmentioning
confidence: 99%